Respostas

2014-07-15T20:26:16-03:00
P(x) = 2x³ - kx + 5x - 1 l__(_x-1_)_____          ⇒        Com resto R = 0
         -2x³+ 2x²              Q(x)=2x²+2x+2-k+5
      --------------------------- 
      2x² - kx +  5x - 1
     -2x² +2x
      ----------------------------
           2x - kx + 5x - 1
          -2x               +2
      ---------------------------- 
                - kx + 5x + 1
                  kx  - k   
      ---------------------------------
                        5x - k + 1
                       -5x      + 5
      ---------------------------------
           R               - k  + 6 = 0     ⇒  k = 6 (resposta)
1 5 1